Valentino’s syndrome: a curious case of perforated peptic ulcer mimicking acute appendicular perforation, a case report and comprehensive literature review - Kumar, Supreet; Bhalerao, Aishwarya S.; Tandon, Vivek; Govil, Deepak (International Surgery Journal, 2025)
Valentino’s syndrome is an uncommon presentation of perforated peptic ulcer disease where the contents of the stomach and duodenum can trickle through the right paracolic gutter and imitate the classic signs of acute appendicitis. This atypical presentation poses a significant diagnostic challenge, especially in older patients with several health issues. We describe the case of a 74-year-old lady having a history of uncontrolled diabetes, hypertension, hypothyroidism, and allergic airway disease. She presented with a sudden onset of mid-abdominal pain that soon localized to the right lower quadrant, accompanied by gradual distention of abdomen, nausea, and a single episode of bilious vomiting. The initial imagining was not confirmatory and only suggested a hollow viscus perforation, the findings pointing towards a probable appendicular perforation. An emergency laparotomy revealed a normal appendix and caecum, with further exploration uncovering a partially sealed 2×2 cm partially sealed pre-pyloric perforation. A modified Graham patch repair was performed, and a feeding jejunostomy was placed to support her recovery given her frail condition. Surgical findings were contrary to the findings noted on the cross-sectional imaging and led to a revision of diagnosis surprisingly from an anticipated appendicular perforation to a perforated peptic ulcer. After a thorough peritoneal lavage, the prepyloric perforation was repaired using a modified Graham’s technique, with supportive measures in the form of a feeding jejunostomy that contributed to her gradual recovery. Histopathological analysis confirmed chronic inflammation and the patient’s postoperative course was steady and uneventful. This case highlights the importance of considering Valentino’s syndrome in elderly patients presenting with right lower quadrant pain. A careful and comprehensive diagnostic approach, aided by modern imaging and thorough surgical exploration, is essential for achieving the best outcomes in these challenging cases.